Instructional quality and achievement inequality: How effective is teaching in closing the social achievement gap?. (October 2019) - Atlay, Cansu; Tieben, Nicole; Hillmert, Steffen; Fauth, Benjamin
Abstract: Previous empirical studies have shown that there is an association between parental socioeconomic status (SES) and educational achievement. Research has also shown that although teaching quality contributes to overall student achievement, it may have differential effects on the learning outcomes of students from lower and higher socioeconomic backgrounds. In this paper, we investigate if teaching quality is associated with the student achievement among students from low and high socioeconomic backgrounds. Using German panel data and multilevel modelling, we examined the interaction between three dimensions of teaching quality (cognitive activation, classroom management and supportive climate) and student background. Our results suggest that, overall, classroom management is positively associated with student performance. Students with high socioeconomic backgrounds seem to profit more from cognitive activation and supportive climate compared to their peers with middle and low socio-economic backgrounds: These two indicators of teaching positively moderated the association between socioeconomic background and achievement levels, thus leading to a larger achievement gap. Highlights: Classroom management had a direct positive association with achievement. Cognitive activation and supportive climate moderate the SES – achievement link. Low SES students may not always be at ease with certain methods in the classroom. Certain aspects of teaching may increase the social achievement gap.